2016
DOI: 10.1038/nature16944
|View full text |Cite
|
Sign up to set email alerts
|

Controlling spin relaxation with a cavity

Abstract: Spontaneous emission of radiation is one of the fundamental mechanisms by which an excited quantum system returns to equilibrium. For spins, however, spontaneous emission is generally negligible compared to other non-radiative relaxation processes because of the weak coupling between the magnetic dipole and the electromagnetic field. In 1946, Purcell realized that the spontaneous emission rate can be strongly enhanced by placing the quantum system in a resonant cavity -an effect which has since been used exten… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
161
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 158 publications
(171 citation statements)
references
References 40 publications
8
161
2
Order By: Relevance
“…The output power depends linearly on P in as long as P in < −131 dBm (blue lines is a linear fit), while the phase shift is zero (blue line) only for P in < −137 dBm. Rabi oscillations (obtained by sweeping the power of the 10-μs rectangular refocusing pulse in the Hahn echo sequence) are used to calibrate the pulses for subsequent experiments [41]. To avoid saturation of AMP as explained in the previous section, we purposely set the field far away from the maximum of the spin resonance line at B 0 ¼ 2.6 mT [see Fig.…”
Section: Esr Spectroscopy In the Presence Of Squeezingmentioning
confidence: 99%
See 1 more Smart Citation
“…The output power depends linearly on P in as long as P in < −131 dBm (blue lines is a linear fit), while the phase shift is zero (blue line) only for P in < −137 dBm. Rabi oscillations (obtained by sweeping the power of the 10-μs rectangular refocusing pulse in the Hahn echo sequence) are used to calibrate the pulses for subsequent experiments [41]. To avoid saturation of AMP as explained in the previous section, we purposely set the field far away from the maximum of the spin resonance line at B 0 ¼ 2.6 mT [see Fig.…”
Section: Esr Spectroscopy In the Presence Of Squeezingmentioning
confidence: 99%
“…6(a)], because decoherence occurs by nonradiative processes such as dipolar interactions [51]. Energy relaxation, on the other hand, has been shown to be caused by spontaneous emission of microwave photons through the cavity (the Purcell effect) with a rate T −1 1 ¼ 4g 2 =κ [41], g being the coupling of a single spin to the radiation field as defined in Sec. II.…”
Section: A Applicability Of the Schemementioning
confidence: 99%
“…To describe this interference effect, an extension of the McCoy and Ernst derivation13, which is based on electrical circuit description with a single nuclear susceptibility affecting the coil inductance, is not straightforward. Instead, in this regime where the contribution from spontaneous emission coupled to the cavity is weak29, we use generalized Bloch equations in which the rf fields include feed-back fields and randomly fluctuating fields12, for which several noise sources were considered: those resulting from the transverse magnetization and those resulting from the electronic Nyquist noise due to the resistive elements of the circuit.…”
Section: Resultsmentioning
confidence: 99%
“…This will be important for hybrid donor-dot quantum computing schemes since the 5 GHz clock transition was recently predicted to form an avoided crossing with silicon based quantum dots 10 . This was discussed in the donor-dot surface code proposal by Pica et al 10 which also suggested addressing the clock transitions using microwave polarization.Bismuth donors in Si have a large hyperfine coupling which not only gives rise to a large zero field splitting, but also allows for rapid manipulation of both the electronic and nuclear spin states when operating in the intermediate field regime where the hyperfine coupling is comparable to the Zeeman splitting 8,[11][12][13] . In this regime we describe the states using the total spin, F , and its projection, m F 6 .…”
mentioning
confidence: 99%
“…Bismuth donors in Si have a large hyperfine coupling which not only gives rise to a large zero field splitting, but also allows for rapid manipulation of both the electronic and nuclear spin states when operating in the intermediate field regime where the hyperfine coupling is comparable to the Zeeman splitting 8,[11][12][13] . In this regime we describe the states using the total spin, F , and its projection, m F 6 .…”
mentioning
confidence: 99%